Specificity and mechanism of ferrioxamine-mediated iron transport in Streptomyces pilosus. - Müller, G (1984)
Although the ferrioxamines are an important and well-characterized class of siderophores produced by several species of Nocardia, Streptomyces, Micromonospora, Arthrobacter, Chromobacterium, and Pseudomonas, no studies of the mechanism of ferrioxamine-mediated iron uptake have been performed for an organism which produces the siderophore. This is the first report of metal transport in Streptomyces pilosus mediated by the native ferrioxamines B, D1, D2, and E. 55Fe accumulation in these ferrioxamines was dependent on metabolic energy and was a saturable process with increasing complex concentration. The apparent Km for [55Fe]ferrioxamine B uptake was approximately 0.2 microM. Both chromic desferriferrioxamine B and [67Ga]desferriFerrioxamine B were transported at rates similar to those of the 55Fe complexes: this implies that no decomplexation or reduction of the metal ion is required for transport, since the chromic complexes are kinetically inert and the gallium complexes have no stable divalent state as a possible reduction product. In addition, isomers of inert chromic desferriferrioxamine B complexes were used to probe the stereospecificity of the ferrioxamine uptake system. The chromic complexes were separated into three fractions by cationic exchange chromatography and assigned as two cis and a (mixture of) trans geometrical isomer(s) by their visible spectra. [55Fe]ferrioxamine B uptake was equally inhibited by each isomer, suggesting that no differentiation between cis and trans geometrical isomers occurs. In the presence of chromic desferriferrioxamine B isomers, the uptake rates for 55Fe-labeled ferrioxamines E, D1, and D2 were even more strongly reduced than was that for [55Fe]ferrioxamine B itself. From these results we conclude that all the ferrioxamines tested are transported into the cells by the same uptake system.